Microscopic study of thermoelectric In-doped SnTe. (27th April 2018) - Nan, Pengfei; Liu, Ruibin; Chang, Yunjie; Wu, Hongbo; Wang, Yumei; Yu, Richeng; Shen, Jun; Guo, Wei; Ge, Binghui
Abstract: SnTe is a p-type thermoelectric material that is isostructural with PbTe, for which it is a potential environmentally friendly replacement. By doping the SnTe lattice with In, the thermal conductivity of SnTe can be significantly reduced and the thermoelectric conversion efficiency improved. A large number of precipitates were present in the In-doped SnTe samples; based on atomic-resolution high-angle annular dark-field images and electron energy loss spectra, these precipitates were identified as the zinc-blende phase of In2 Te3 . Through geometry phase analysis, a new phonon scattering mechanism is discussed.